Brief review of working fluid selection for organic rankine cycle - Husin N.S.; Lim C.W.; Ng K.; Abdullah W.S.W.; Eng K.H.; Koh S.P.; Tiong S.K. (American Institute of Physics Inc., 2024)
The organic Rankine cycle (ORC) is proven to be one of the environmentally friendly approaches in improving energy generation, waste heat energy recovery, and medium-low-temperature heat utilization. Waste heat recovery and low-grade heat utilization are important measures to solve the problem that occurred from energy consumption. Working fluid plays an important role in the performance of ORC. This study conducted a quick literature review on the working fluid selection for the ORC system. This brief review analyzed the influence of working fluid category, thermodynamic properties, and physical properties as well as the relevant limitations on the performance of ORC. The safety level and environmental aspect of common working fluids for ORC were also reviewed. The findings indicate that R11, R141b, R113, R123, R124, R600, and R601 have slightly higher performances but R600 are flammable. However, R245fa is the most environmentally friendly working fluid for waste heat recovery applications. In this study, the working fluids selection criteria for the ORC system have been reviewed. This study helps in identifying the potential organic fluids for various ORC applications especially in waste heat recovery from low-temperature heat sources. 2023 Author(s).